The Jungle Grows Back. How Can We Redefine the Future World Order in the Tension of Power and Ideas? - Marsili, M. (Political Reflection Magazine, 2020)
Thirty years after the fall of the Berlin Wall, peace and stability are challenged every day. The Russian intervention in Ukraine and Georgia (Marsili, 2016), the economic expansion of the People's Republic of China (Marsili, 2015), the nuclear threat from Iran and the Democratic People's Republic of Korea, the revisionism of the United States (U.S.), and, last but not least, hybrid threats such as international terrorism, jeopardize the world order (Marsili, 2019). The maintenance of world order is the main concern of the international community (Bull, 1997). The cardinal points of international law are lost, and the rule of law is a ghost that wanders around the world: are we back to the jungle? How can we redefine the future world order in the tension of power and ideas?